Acehnese Women in Public Spaces: Theirmovement and Political Participation - Inayatillah, Inayatillah (Jurnal Ilmiah Peuradeun, 2023)
Aceh has the most enduring legacy of successful female leaders in the world. The situation has changed during the past few decades, as fewer women hold crucial government positions. This paper traced the history of women and their role in Aceh through colonial and post-colonial contexts from the early years of this century to the present day. This study also examined the role and contributions made by the Acehnese women through the women's movement and their participation in political life, as well as the reasons for the lack of women appointed as policymakers, as indicated by multiple studies on this topic. A qualitative library research method was employed, and the data from text documents were analyzed using critical discourse analysis. The research showed that women in Aceh continued to play an essential role in the public domain and made significant contributions through the movement. However, The lack of opportunity for women to occupy their position as policymakers were influenced by diverse issues ranging from the patriarchal culture in Aceh, the inability of a political party to cadre women, to the misconception of people in interpreting religious belief that women should not be allowed to be a leader.